MENINGKATKAN KEMAMPUAN MEMBACA KATA MELALUI MEDIA POWER POINT BAGI ANAK TUNARUNGU KELAS 1 SDLB DI SLB BINTAN - Supeni - Nugrahawati (Universitas Negeri Padang, 2013)
This study aims to improve the reading skills of students with hearing impairment grade I said SLB Bintan through the application of media power point. This study is an action research (classrooms action research) with a research design Sudarsono. Subjects were two deaf students grade I SLB Bintan. The study consisted of 2 cycles. The first cycle consists of 5 rooms and the second cycle consists of 3 meetings. Each cycle ends with a post-test. Implementation of the second cycle based on the evaluation performed in the first cycle, the research has not achieved the success criteria specified. Cycle II is an improvement action cycle I. Data collection is done by testing the ability to read words and observations. The method of data analysis is descriptive quantitative and presentation of data in tables and graphs histogram. The results showed that the application of medi da power point can improve deaf students' reading skills. The result is evidenced by the increasing achievement scores by students' reading comprehension skills. Improved reading comprehension ability of deaf students 'achievement scores indicated by increasing students' ability to pronounce words, naming objects, and matching words with pictures. Improving students' reading skills through the application of media Deaf power point and the students were given verbal motivation and praise to encourage increased capabilities. The final conclusion is through the application of media power point deaf students' reading skills improved.